2009
DOI: 10.1143/jjap.48.03a042
|View full text |Cite
|
Sign up to set email alerts
|

109 Gbit/in.2 Recording on Near-Field Optical Disc Using Combination of Partial-Response Channel and Low-Density Parity-Check Code

Abstract: We discuss the condition necessary for the H a m s criterion to be valid on hierarchical lattices. We prove that disorder is always relevant when the specific heat exponent, ap, is positive and show how to construct lattices for which disorder becomes relevant while ap is still negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] It can exhibit a large capacity and a highdata transfer rate towards recording next-generation ultrahigh-definition television [i.e., Super Hi-Vision (SHV), 7320 Â 4320 pixels] video signals 17,18) for home-use. Fourfold higher density recording using NFR optical disks with 1.2-mm-thick disks has been reported, 12,14) and studies of larger capacity using multilayer recording using NFR have been reported. 15,16) If the NFR media can realize 250-Mbpsclass high-speed recording and two-or three-layer recording, the SHV optical media, which has more than two hours recording ability would be able to be realized.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] It can exhibit a large capacity and a highdata transfer rate towards recording next-generation ultrahigh-definition television [i.e., Super Hi-Vision (SHV), 7320 Â 4320 pixels] video signals 17,18) for home-use. Fourfold higher density recording using NFR optical disks with 1.2-mm-thick disks has been reported, 12,14) and studies of larger capacity using multilayer recording using NFR have been reported. 15,16) If the NFR media can realize 250-Mbpsclass high-speed recording and two-or three-layer recording, the SHV optical media, which has more than two hours recording ability would be able to be realized.…”
Section: Introductionmentioning
confidence: 99%
“…A near-field optical recording (NFR) system using a solid immersion lens (SIL) 1) has a fourfold higher recording density than the Blu-ray disc system. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Some studies have shown the realization of a large recording capacity using multilayer recording techniques for optical disks, [17][18][19][20][21] but the data transfer rate is limited. The NFR system is expected to realize not only a large capacity but also a high data transfer rate because its numerical aperture (NA) is more than two times higher and the optical beam spot can be less than half the diameter of current Blu-ray optical systems.…”
Section: Introductionmentioning
confidence: 99%
“…The NFR system has more than four times higher recording density than the Blu-ray disc system. [2][3][4][5][6][7][8][9][10][11][12][13][14] Multilayer recording techniques for optical disks 15,16) is effective for realizing a large capacity, but the data transfer rate is limited as the mark size, which is caused by the numerical aperture (NA) of the 0.85-Blu-ray disc system. NFR techniques using SIL have more than two times higher NA than Blu-ray disc and have the feasibility of achieving more than two times higher data transfer rate recording at the same disk rotational speed; however, the feasibility of high-data-transfer-rate recording of more than 200 Mbps using NFR techniques with narrow-track pitch disks has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%